1988
DOI: 10.1002/jlb.43.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Oxidized by Polymorphonuclear Leukocytes Inhibits Natural Killer Cell Activity

Abstract: We studied the effect of low-density lipoprotein (LDL) oxidized by opsonized zymosan-stimulated polymorphonuclear leukocytes (PMN) on natural killer (NK) cell activity. Oxidized LDL inhibited NK cell activity in a dose-dependent manner, whereas normal LDL left it unaffected. However, oxidized LDL did not inhibit antibody-dependent cell-mediated cytotoxicity (ADCC). Moreover, a positive correlation was observed between the amount of thiobarbituric acid-reacting substances (TBARS) on the sample of oxidized LDL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Thus, the a-tocopherol content was sufficient to protect HDL from lipid peroxidation, despite oxidative stress. These finding are consistent with previous studies, which showed that PMN caused less oxidation of HDL than of LDL [32]. However, a recent study of HDL oxidation using chemical oxidizing systems (Cu'+) detected no large variations in classical oxidative monitors such as TBARS, even though oxidized cholesterol derivatives emerged [33].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the a-tocopherol content was sufficient to protect HDL from lipid peroxidation, despite oxidative stress. These finding are consistent with previous studies, which showed that PMN caused less oxidation of HDL than of LDL [32]. However, a recent study of HDL oxidation using chemical oxidizing systems (Cu'+) detected no large variations in classical oxidative monitors such as TBARS, even though oxidized cholesterol derivatives emerged [33].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, a delayed clearance of LDL from the plasma due to unimpaired receptor function renders this molecule more susceptible to modifications which have been demonstrated to be involved in the transformation of macrophages to foam cells [1][2][3]. Recently, several reports [3][4][5][6]8] have shown that free radicals produced by stimulated PMN and macrophages (N-formyl-L-methionyl-Lleucyl-L-phenylalanine (fMLP), PMA, or zymosan) avidly modified LDL. This oxLDL is overlooked by normal LDLR interacting only with scavenger receptors [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…This oxLDL is overlooked by normal LDLR interacting only with scavenger receptors [3,11]. OxLDL altered lymphocyte and macrophage proliferative and cytotoxic responses [3][4][5][6][7][8], suggesting that this is one of the key physiopathological events in atheroma formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations